A filosofia da literatura de Kuki Shūzō e como podemos ler/traduzir a filosofia japonesa - Diogo César Porto da Silva (2020)
Having as our main goal an inquiry on Japanese philosopher Kuki Shūzō’s (1888-1941) philosophy regarding literature, we will focus on pointing out the connections, within his writings, between contingency and method, philosophy, and literature as well as West and East. Taking as the core objects of our analysis the works The Problem of Contingency (Gūzensei no Mondai) (1935) and Philosophy of Literature (Bungeiron) (1941), we aim to not only claim the central role of literature in his philosophy as a whole but also that his philosophical strategies allow us to think him as an important philosopher of difference whose goal was to demonstrate the philosophical relevance of rhyme and surprise. In order to pursue our goals, we developed a comparative philosophy strategy that seeks to explore the potential for otherness hidden in Western philosophy. Looking upon two of the most basics activities of the philosophical doing, reading and translating, we hope to reach a philosophical approach that could be more dialogical and responsible toward the otherness of the non-Western. Through this comparative philosophy strategy, we will deal with Kuki’s texts.